miRNA-221: A Potential Biomarker of Progressive Liver Injury in Chronic Liver Disease (CLD) due to Hepatitis B Virus (HBV) and Nonalcoholic Fatty Liver Disease (NAFLD) - Parthana Rani Sutradhar; Nahida Sultana; Afzalun Nessa (International Journal of Hepatology)
Conclusion: miRNA-221 may be used as a potential plasma biomarker for early prediction of fibrosis progression in CLD patients.